Causes of death in children with congenital anomalies up to age 10 in eight European countries - Mika Gissler; Maria Loane; Ingeborg Barisic; Hermien E K de Walle; Miriam Gatt; Kari Klungsoyr; Anna Pierini; Anke Rissmann; Oscar Zurriaga; Diana G Wellesley; Clara Cavero-Carbonell; Olatz Mokoroa; et al. (BMJ Publishing Group, 2023)
Background Congenital anomalies (CAs) increase the risk of death during infancy and childhood. This study aimed to evaluate the accuracy of using death certificates to estimate the burden of CAs on mortality for children under 10 years old.Methods Children born alive with a major CA between 1 January 1995 and 31 December 2014, from 13 population-based European CA registries were linked to mortality records up to their 10th birthday or 31 December 2015, whichever was earlier.Results In total 4199 neonatal, 2100 postneonatal and 1087 deaths in children aged 1-9 years were reported. The underlying cause of death was a CA in 71% (95% CI 64% to 78%) of neonatal and 68% (95% CI 61% to 74%) of postneonatal infant deaths. For neonatal deaths the proportions varied by registry from 45% to 89% and by anomaly from 53% for Down syndrome to 94% for tetralogy of Fallot. In children aged 1-9, 49% (95% CI 42% to 57%) were attributed to a CA. Comparing mortality in children with anomalies to population mortality predicts that over 90% of all deaths at all ages are attributable to the anomalies. The specific CA was often not reported on the death certificate, even for lethal anomalies such as trisomy 13 (only 80% included the code for trisomy 13).Conclusions Data on the underlying cause of death from death certificates alone are not sufficient to evaluate the burden of CAs on infant and childhood mortality across countries and over time. Linked data from CA registries and death certificates are necessary for obtaining accurate estimates.